2019
DOI: 10.1029/2019tc005496
|View full text |Cite
|
Sign up to set email alerts
|

Geodetic Evidence of High Compression Across Seismically Active Kachchh Paleorift, India

Abstract: In the past 200 years, the Kachchh paleorift in western India, a plate interior region, has witnessed unusually large number of strong earthquakes, namely, the 2001 Bhuj (Mw 7.6), 1956 Anjar (Mw 6.0), 1845 Lakhpat (Mw ~6), and 1819 Allah Bund (Mw ~7.7) earthquakes. We report continuous GPS measurements from the Kachchh and adjoining region. We find that the ongoing deformation during 2009–2016 is inconsistent with the models of postseismic deformation due to the 2001 Bhuj earthquake. The current widespread def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…Also, a slower moving Marwar Craton would lead to compression across the Kachchh failed rift (figure 8 ), which would be consistent with the GPS measurements across the Kachchh failed rift (Gahalaut et al . 2019 ).
Figure 8 A schematic cartoon showing the Marwar and Bundelkhand cratons modified after Vijaya Rao et al .
…”
Section: A Hypothesised Tectonic Model For Seismogenesis In the Adfbmentioning
confidence: 99%
“…Also, a slower moving Marwar Craton would lead to compression across the Kachchh failed rift (figure 8 ), which would be consistent with the GPS measurements across the Kachchh failed rift (Gahalaut et al . 2019 ).
Figure 8 A schematic cartoon showing the Marwar and Bundelkhand cratons modified after Vijaya Rao et al .
…”
Section: A Hypothesised Tectonic Model For Seismogenesis In the Adfbmentioning
confidence: 99%
“…We deduce that the higher displacement rate in the flanks is mainly responsible for the accumulation of more strain in the central part of KRB and the presence of high seismicity towards the central part of KRB supports our deduction. A study (Gahalaut et al, 2019) found a good correlation between geodetic moment rate and seismic moment release rate. Furthermore, an accumulation of maximum strain of 5 nano-strain/ year is observed in the vicinity of the 2001 earthquake epicentre (Dumka et al, 2019).…”
Section: Grace Observationsmentioning
confidence: 98%
“…The outliers were down-weighted from the generated time-series (Figure S1) to obtain a consistent set of coordinates for the velocity estimation. Furthermore, the results of (Dumka et al, 2019;Gahalaut et al, 2019) were jointly analysed with the results of present study.…”
Section: Gnss Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dumka et al (2018) proposed that even a very small reservoir can influence the deformation and may antrigger earthquake. Gahalaut et al (2019) analysed the crustal deformation across the Kuchchh paleo rift to suggest that the paleo-rift is under excessive compression.…”
Section: Seismotectonic Studiesmentioning
confidence: 99%